Prolonged fasting‐induced hyperketosis, hypoglycaemia and impaired fat oxidation in child and adult patients with spinal muscular atrophy type II. (30th August 2021) - Ørngreen, Mette Cathrine; Andersen, Annarita G.; Eisum, Anne‐Sofie; Hald, Emma J.; Raaschou‐Pedersen, Daniel E.; Løkken, Nicoline; Høi‐Hansen, Christina E.; Vissing, John; Born, Alfred P.; van Hall, Gerrit
Abstract: Aim: This study explored hypoglycaemia and metabolic crises, including hyperketosis, in patients with spinal muscular atrophy (SMA). Methods: The study comprised four adolescents aged 15–17 and six adults aged 19–37 with SMA type II and eight adult controls aged 21–41, who were recruited by the Rigshospitalet, Denmark, from May 1st to October 30th 2017. We used stable isotope technique and indirect calorimetry to investigate fat and glucose metabolism during a 24‐h fast or until hypoglycaemia occurred. Results: All patients with SMA II developed moderate to severe hyperketosis and 60% had symptoms of hypoglycaemia or blood glucose levels below 3 mmol/L. None of the controls developed hyperketosis or hypoglycaemia. Plasma bicarbonate decreased, in line with increased ketone bodies, indicating the start of metabolic acidosis in patients with SMA II. Increased fat production and utilisation were seen in healthy controls during the fasting period, but were absent in patients with SMA II, indicating blunted fat oxidation. Conclusion: Low skeletal muscle mass was the best explanation for why patients with SMA II had an increased risk of hypoglycaemia, hyperketosis, metabolic acidosis and disturbed fat and glucose metabolism during fasting. These risks have implications for children facing surgery and those with severe illnesses.